2016
DOI: 10.1016/j.ejogrb.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Age related normogram for antral follicle count in general population and comparison with previous studies

Abstract: The current age related nomogram presented a steady decline in AFC that became significant after 35 years in otherwise healthy women with regular menstrual bleeding. Those percentiles might be used as a reference guide to point out the current status of ovarian reserve for a given woman. Additionally, producing nomogram might enforce using percentiles instead of constant thresholds to define various medical conditions such as polycystic ovarian morphology or diminished ovarian reserve. However, longitudinal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…However, studies indicate that at any given age, there is a considerable variation in serum AMH levels ( 14 , 17 , 18 ). Thus, similar to what has been observed for antral follicle count (AFC), large interindividual variation exists for AMH levels ( 19 , 20 ). Ethnicity may contribute to this variation and should be taken into account when interpreting AMH values.…”
Section: Serum Amh Levels In the General Populationsupporting
confidence: 66%
“…However, studies indicate that at any given age, there is a considerable variation in serum AMH levels ( 14 , 17 , 18 ). Thus, similar to what has been observed for antral follicle count (AFC), large interindividual variation exists for AMH levels ( 19 , 20 ). Ethnicity may contribute to this variation and should be taken into account when interpreting AMH values.…”
Section: Serum Amh Levels In the General Populationsupporting
confidence: 66%
“…A prospective cross-sectional study included 381 women aged 20-50 years with regular menstrual cycle and count number of AFC based on transvaginal ultrasound in the early follicular phase. The result showed that there were no significant differences in AFC among different age groups under 35 years, whereas a significant decrease after 35 years [23]. Bishop et al analyzed the relationship between live birth and ovarian reserve in 9489 cycles among 8214 patients aged 21-44 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that, on average, POSEIDON patients had a higher BMI and, more often, a female infertility factor associated with this condition (versus non-POSEIDON). The relationship between female age, ovarian markers and ART reproductive success is well-established ( 31 33 ), and BMI has been shown to influence the number of oocytes retrieved and embryos obtained, as well as pregnancy outcomes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%